Evaluation of performance by government functions through the PROMETHEE II method - Bezerra, Victor Vidal de Negreiros; de Carvalho, José Ribamar Marques (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
The performance evaluation has shown to be an important tool for the development and improvement of public management in the municipal context. In this sense, the present study seeks to cooperate to develop and improve municipal performance evaluations through multicriteria decision support techniques. Based on the per capita expenditure indicators in the 28 government functions, this study aims to verify the performance of the municipalities belonging to Paraíba micro-regions of Campina Grande and Esperança regarding government spending. By testing PROMETHEE II multicriteria method, it was possible to identify its applicability in the context of evaluation performance of municipalities. Esperança and Boa Vista were the ones that stood out the most in the performance ranking, while the municipalities of Massaranduba and Fagundes occupied the last two positions in the years 2014 and 2015. This comparative evaluation is understood to be useful for highlighting which are the municipalities that have excelled in the management of public resources. In addition, this type of analysis allows state managers, federal managers and control bodies to identify which municipalities need more monitoring and resources to meet the needs of the local population.